دور قسم علوم التربية في تنمية قيم المواطنة لدى الطلبة في جامعة الجزائر 2 - طوبال, جمال (جامعة الوادي - University of Eloued, 2022)
هدف البحث الحالي التعرّف لدور قسم علوم التربية في كلية العلوم الاجتماعية في جامعة الجزائر 2 في تنمية قيم المواطنة لدى طلبته، وذلك من وجهة نظر الطلبة أنفسهم. اعتمد الباحث على المنهج الوصفي، وكانت أداة البحث استبانة، طُبّقت على عَيّنة مؤلفة من (95) طالباً وطالبةً في قسم علوم التربية في جامعة الجزائر 2، (55) طالباً من طلبة السنة الثالثة: تخصص علم النفس التربوي، و (40) طالباً من طلبة الماستر 1: تخصص أنظمة تعليم ومناهج دراسية، تم تطبيق الدراسة الميدانية في الفصل الدراسي الثاني من العام الدراسي 2020/2021 وتم استخدام المتوسطات الحسابية والانحرافات المعيارية لتحليل البيانات. أكدت نتائج البحث أن قسم علوم التربية في جامعة الجزائر 2 يؤدي دوره على أتم وجه في تنمية قيم المواطنة لدى طلبته وبدرجة مرتفعة. أما على المحاور الفرعية للاستبانة، فكانت مساهمة المناخ التعليمي، والأستاذ الجامعي مرتفعة، في حين كانت مساهمة إدارة الكلية في تنمية قيم المواطنة لدى الطلبة متوسطة. كما أكدت نتائج البحث عدم وجود فروق في وجهات نظر الطلبة حول موضوع مساهمة القسم في تنمية قيم المواطنة لديهم. بناءً على نتائج البحث، قدم الباحث مجموعة من المقترحات، أهمها: إدراج مقررات جامعية (أو فصول ضمن كتب جامعية) عن قيم المواطنة وكيفية تنميتها، وعقد ندوات ومحاضرات ودورات تدريبية حول المواطنة وسبل تنميتها لدى الشباب الجزائري . Abstract: The aim of the current research is to identify the role of the Department of Education Sciences at the Faculty of Social Sciences at the University of Algiers 2 in developing the values of citizenship among its students, from the students' point of view. The researcher adopted the descriptive approach, and the research tool was a questionnaire, which was applied to a sample of (95) students in the Department of Education Sciences at the University of Algiers 2, (55) students from the third year: educational psychology, and (40) students from among the students Master 1: specializing in education systems and curricula. The field study was applied in the second semester of the academic year 2020/2021 and arithmetic averages and standard deviations were used to analyze the data. The results of the research confirmed that the Department of Education Sciences at the University of Algiers 2 plays its role in developing the values of citizenship among its students. As for the sub-axes of the questionnaire, the contribution of the educational climate and the university professor was high, while the contribution of the college administration in developing the values of citizenship among students was moderate. The results of the research also confirmed that there are no differences in the students' views on the topic of the department's contribution to the development of their citizenship values according to the variables of specialization. Based on the results of the research, the researcher presented a set of proposals, the most important of which are: the inclusion of university courses (or chapters within university books) on citizenship and how to develop it, holding seminars, lectures and training courses on citizenship and ways to develop it among Algerian youth.
مقال
Keywords: المواطنة؛ قيم المواطنة؛ كلية العلوم الاجتماعية؛ قسم علوم التربية؛ جامعة الجزائر 2; Citizenship - Values of citizenship - Faculty of Education – Algeria2 University